Clinical implications of trichomonads detected in bronchoalveolar fluid by metagenomic next-generation sequencing: a multicenter retrospective study - Jiang, Juan; Li, Yuanyuan; Wang, Qiong; Zeng, Huihui; Yang, Wei; Wu, Yanhao; Peng, Wenzhong; Pan, Pinhua; Hu, Chengping; Deng, Pengbo (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Pulmonary trichomoniasis is considered a neglected disease due to failures in recognizing it, stemming from insensitive microbial methods and a lack of specific clinical features. This study aims to analyze the clinical implications of trichomonads detected in bronchoalveolar lavage fluid (BALF) by metagenomic next-generation sequencing (mNGS). Methods: This multicenter retrospective study included patients diagnosed with pneumonia, admitted to three tertiary hospitals in China from July 2018 to September 2022, with trichomonads detected in BALF through mNGS. The analysis covered demographics, comorbidities, symptoms, laboratory findings, mNGS results, clinical treatment, and outcomes of these patients. Results: A total of 17 patients were enrolled, comprising 14 males and 3 females. Trichomonas tenax and Trichomonas vaginalis were detected by mNGS in BALF samples of 15 and 2 patients, respectively. Patients were categorized into two groups based on the presence of risk factors for trichomonad infection, including immunocompromised conditions, uncontrolled diabetes mellitus, oral/periodontal diseases, and aspiration. Among 11 patients with risk factors (Case 1-11), 4 received nitromidazoles as part of comprehensive treatment, achieving a 100% treatment success rate. The remaining 7 patients, who did not receive nitromidazoles, had only one achieving relief after broad-spectrum antimicrobial therapy, resulting in a 14.3% treatment success rate. For the 6 patients without any risk factors for trichomonad infection (Case 12-17), none received nitromidazoles during hospitalization. However, 4 out of these 6 patients (66.7%) eventually recovered. Conclusions: mNGS proves to be an efficient tool for detecting trichomonads in BALF samples. Comprehensive analysis of clinical features and laboratory indicators is essential to distinguish between infection and colonization of trichomonads. Pulmonary trichomoniasis should not be overlooked when trichomonads are detected in BALF from patients with risk factors.